A review: novel nanohybrids of epoxy/polyamide with carbon nanotube/nano-diamond. Issue 6 (13th April 2021) - Ahmed, Waqas; Gul, Sagheer; Awais, Muhammad; Hassan, Zia Ul; Jabeen, Saira; Farooq, Muhammad
ABSTRACT: This review encompasses detailed knowledge about recent advancement in the synthesis of novel Nanohybrids. The materials based on matrix component as epoxy and Polyamide with the specified carbon nano-bifiller carbon nanotubes and nano-diamond have been discussed in detail due to their novelty and endless applications in various industries. Limited research have been carried out regarding synthesis of epoxy/polyamide-based carbon nanofillers, due to difficulty in processing these type of materials. The review addresses various drawbacks and limitations faced during synthesis of such novel materials. These materials however have many important and demanding applications in electrical, automotive and aerospace industries.